(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research aims to identify the relationship between manifestations of social cohesion and addiction to social networking sites through the relationship of the individuals association with his family, educational institutions, religious institutions, and public social institutions, with addiction to social networking sites. An appropriate methodology has been adopted for the purpose of the research, represented by the analytical descriptive approach, and the social survey method using the sample method. The questionnaire was also used as a tool to collect data on the respondents, which was designed according to the five-point lickert scale as atool for measuring the level of addiction to social networking sites and its relationship to social cohesion. The original research community consisted of fourth- year students (male and female) from the Department of sociology, at the University of Damascus, whose number for the academic year 2022-2023 was /547/ students. The sample size, which was taken by the purposive method, was (70) male and female students. And based on the statistical analysis of the data that was carried out through the statistical program (SPSS) using percentages, average, and Pearson correlation coefficient, a number of results were reached indicting that there is a statistically significant negative correlation between the individuals attachment to his family and addiction to social networking sites. The results also showed that there is a statistically negative correlation between the individuals attachment to the educational institution and addiction to social networking sites. The results also indicated that there is a statistically negative correlation between the individuals attachment to the religious institutions and addiction to social networking sites. The results also showed that there is a statistically negative correlation between the individuals attachment to public social institutions and addiction to social networking sites. Thus, there is a relationship between social cohesion and addiction to social cohesion and addiction to social networking sites.